Body language and the first line manager - Lawton, Eunice; ScienceDirect eBooks (Oxford : Chandos, 2006)
Body language can account for 70 per cent of the message we give out. This book provides an insight into the impact that body language can have at work. It is aimed at first line management level and provides a look at body language and how we need to ensure that we are giving out the right non-verbal messages in different management situations.
Cover; Body Language and the First Line Manager; Copyright; Contents; Preface; About the author; Body language and the first line manager; Introduction; The importance of non-verbal communication; First impressions; Your image at work; Achieving assertiveness; Raising your profile; Body language basics; Building rapport; Meeting and greeting people; Presentation skills; Team meetings and briefings; Attending meetings; Gaining cooperation; Staff appraisal; Negotiating skills; Attending interviews; Other cultures; Putting non-verbal communication into practice; Further reading; Index.
Includes bibliographical references (page 75) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Interpersonal communication; Body language; Communication interpersonnelle; Langage du corps; PSYCHOLOGY -- Cognitive Psychology; SCIENCE -- Cognitive Science; Body language; Interpersonal communication; Electronic books